MINI BODY1, encoding a MATE/DTX family transporter, affects plant architecture in mungbean (Vigna radiata L.) - Li, Xin; Jia, Yahui; Sun, Mingzhu; Ji, Zikun; Zhang, Hui; Qiu, Dan; Cai, Qiao; Xia, Yan; Yuan, Xingxing; Chen, Xin; Shen, Zhenguo (Frontiers in Plant Science, 2022)
It has been shown that multidrug and toxic compound extrusion/detoxification (MATE/DTX) family transporters are involved in regulation of plant development and stress response. Here, we characterized the mini body1 (mib1) mutants in mungbean, which gave rise to increased branches, pentafoliate compound leaves and shortened pods. Map-based cloning revealed that MIB1 encoded a MATE/DTX family protein in mungbean. qRT-PCR analysis showed that MIB1 was expressed in all tissues of mungbean, with the highest expression level in the young inflorescence. Complementation assays in Escherichia coli revealed that MIB1 potentially acted as a MATE/DTX transporter in mungbean. It was found that overexpression of the MIB1 gene partially rescued the shortened pod phenotype of Arabidopsis dtx54 mutant. Transcriptomic analysis of the shoot buds and young pods revealed that expression levels of several genes involved in phytohormone pathway and developmental regulators were altered in the mib1 mutants. Our results suggested that MIB1 plays a key role in the control of plant architecture establishment in mungbean.